Articulate Storyline as an Interactive Learning Medium: A Critical Literature Review - Haerul Syam; Tatik Retno Murniasih; Farman Farman; Fatqurhohman Fatqurhohman (Review of Education, Science, and Technology, 2025)
Articulate Storyline is an interactive learning medium increasingly utilized in the digital transformation of education due to its capacity to present dynamic content and enhance learner engagement. This article aims to critically examine the use of Articulate Storyline, analyze its contributions to strengthening 21st-century skills, and identify its challenges as well as future development directions. This study employs a critical literature review approach, which not only synthesizes previous findings but also evaluates research trends, contributions, and limitations to reveal remaining research gaps. The review indicates that Articulate Storyline can improve learning motivation, cognitive effectiveness, and support the development of critical thinking, creativity, collaboration, and communication skills. However, issues such as limited digital infrastructure, insufficient teacher technological literacy, and the integration of character development remain significant challenges. These findings highlight the need for more adaptive, collaborative, and inclusive media strategies to ensure equitable benefits across various educational contexts. The novelty of this study lies in formulating a conceptual framework that positions Articulate Storyline as a strategic medium for advancing 21st-century education.